Economic Determinants of Exchange Rate Volatility in Kenya - Kemboi , Isaacks; Kosgei , David K. (African Journal of Education,Science and Technology (AJEST), 2018)
Exchange rate volatility is the focus in determining the economic performance of any particular country. Therefore, there is need in understanding of the concept of exchange rates, extend of causality of exchange rate volatility and their operations in domestic and foreign currencies exchange. Despite abundant empirical literature on the effects of exchange rate volatility on macroeconomic variables, such as, economic growth in many developing open economies like Latin America and Asia, few studies have investigated the determinants of exchange rate volatility. This study looked at the effects of interest rate and inflation rate differentials on the exchange rate volatility of Kenya Shillings relative to the USA dollar. The study used time series data, collected monthly for 175 months from January 2000 to July 2014 from various publications and websites of the Central Bank of Kenya, Kenya National Bureau of Statistics (KNBS) and the US Federal reserve. The data consisted of KSH/USD Exchange rate, 3-month Treasury bills and inflations rates of US and Kenya, collected. Regression analysis revealed that interest rate differential (β =0.826) and inflation rate differential (β=.0.05) had a significant and positive effects on the exchange rate. The results implied that higher interest rates in the country cause a depreciation of the Kenya shillings, which was contrary to interest rate parity (IRP) theory. The study further found that an increase in inflation rate differential causes an increase in exchange rate, which was found to be in agreement with the purchasing power parity (PPP) theory. This study therefore recommends the adoption of suitable policies that seek to stabilize interest and inflation rates and reduce associated pressures to safeguard volatile exchange rate movement.